2008
DOI: 10.1093/gerona/63.7.707
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Lack of Energy (Anergia) Among Elders in a Multiethnic Community

Abstract: Anergia in multiethnic older adults is associated with a range of clinical symptoms and diseases, with extensive health services use, and with increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 46 publications
1
50
0
2
Order By: Relevance
“…Several cross-sectional studies have shown associations between depression or depressive symptoms and fatigue (17,135) and development of fatigue (15,136,137). However, when adjusting the associations between fatigue and diverse outcomes by depressive symptoms, the results did not seriously change (33,58,62,64).…”
Section: Depressionmentioning
confidence: 77%
See 4 more Smart Citations
“…Several cross-sectional studies have shown associations between depression or depressive symptoms and fatigue (17,135) and development of fatigue (15,136,137). However, when adjusting the associations between fatigue and diverse outcomes by depressive symptoms, the results did not seriously change (33,58,62,64).…”
Section: Depressionmentioning
confidence: 77%
“…This is seen specifically for musculoskeletal diseases (78,79,81), but also for neurological and cardiovascular diseases (78), bronchitis, glucose intolerance and arteriostenosis (81) and abdominal syndromes (upper dyspepsia and irritable bowel syndrome) (82). A few longitudinal studies also found that comorbidity (80) and some specific diseases were predictive of onset of fatigue, e.g., respiratory symptoms and urinary incontinence (15) and infections (common cold, flu-like illness, gastroenteritis) (71).…”
Section: The Disease Explanationmentioning
confidence: 98%
See 3 more Smart Citations